2012
DOI: 10.1074/jbc.m111.314823
|View full text |Cite
|
Sign up to set email alerts
|

Deficiency of Cardiolipin Synthase Causes Abnormal Mitochondrial Function and Morphology in Germ Cells of Caenorhabditis elegans

Abstract: Background: Cardiolipin is required for maintaining optimal mitochondrial function. Results: Cardiolipin depletion selectively obstructed proliferation, mitochondrial function, and morphology in germ cells. Conclusion: The contribution of cardiolipin to mitochondrial function and morphology varies among the different cell types in vivo.Significance: This provides a biological basis for understanding the different sensitivities of organelles to changes in the lipid environment.Cardiolipin (CL) is a major membra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 61 publications
2
39
0
1
Order By: Relevance
“…Indeed, these mitochondria exhibited increased electron density with less and disorganized cristae (Figure 2e), which is in agreement with previously published results. [33][34][35][36][37] In addition to reduction in cyt c, we also observed a decrease in the protein level of MTCO1 (Figure 2b). A reduction in the amount of this labile protein suggests a defect in respiratory chain complex IV assembly.…”
Section: Resultsmentioning
confidence: 71%
“…Indeed, these mitochondria exhibited increased electron density with less and disorganized cristae (Figure 2e), which is in agreement with previously published results. [33][34][35][36][37] In addition to reduction in cyt c, we also observed a decrease in the protein level of MTCO1 (Figure 2b). A reduction in the amount of this labile protein suggests a defect in respiratory chain complex IV assembly.…”
Section: Resultsmentioning
confidence: 71%
“…In a mouse model for human Barth syndrome which is characterized by low tetralinoleoyl CL levels mitochondrial morphology as well as cristae ultrastructure were greatly distorted [55]. Cristae alterations were further observed in C. elegans when CL synthesis is impaired [56]. Taken together, APOOL may well be required for proper transport of CL e.g.…”
Section: Discussionmentioning
confidence: 96%
“…A strain carrying a mutation in crls-1, the homolog of cardiolipin synthases, produced a very small brood compared with wild type. Further studies revealed defects in germ cell proliferation in the crls-1 mutants, even though somatic cells divided normally in the same animals (Sakamoto et al 2012). This suggests that the contribution of cardiolipin to mitochondrial function varies among cell types and indicates that proper membrane lipid composition in mitochondria is vital for the optimal proliferation of germ cells.…”
Section: Lipid Synthesis In Gametogenesis and Fertilization In Drosopmentioning
confidence: 99%